2019
DOI: 10.2519/jospt.2019.8763
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Performance After the Return to Run Clinical Pathway in Patients Using the Intrepid Dynamic Exoskeletal Orthosis

Abstract: Background Severe ankle and foot injuries in the US military can result in high-level functional limitation, lost duty days, and medical discharge. Objective To assess the effectiveness of the Return to Run Clinical Pathway (RTR) in returning patients with lower extremity fractures who utilized the Intrepid Dynamic Exoskeletal Orthosis (IDEO) to high-level mobility. Methods Thirty servicemembers with lower extremity fractures who utilized the IDEO unilaterally and completed the RTR at Naval Medical Center San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thus, complex agility is likely not comparable, but single-plane agility may be more achievable. Additionally, a prior study looking at agility gains before and after the PD-AFO in patients with unilateral lower extremity fractures found that overall total CHAMP scores improved [9]. So although these patients may run with less agility compared with uninjured, full-duty runners, they still likely improve in agility compared with their own postinjury baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complex agility is likely not comparable, but single-plane agility may be more achievable. Additionally, a prior study looking at agility gains before and after the PD-AFO in patients with unilateral lower extremity fractures found that overall total CHAMP scores improved [9]. So although these patients may run with less agility compared with uninjured, full-duty runners, they still likely improve in agility compared with their own postinjury baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed high-level mobility with the CHAMP in patients with lower extremity fractures utilizing the IDEO [21]. Patients participated in a rehabilitation program called the Return to Run Clinical Pathway.…”
Section: Discussionmentioning
confidence: 99%
“…No significant changes were noted in the SLS, ESST or IAT. Our population contained only HELET patients, while the study from Mazzone also contained patients with less severe injuries (e.g., stress fractures) [21]. They might have obtained higher scores on the tests without the brace, resulting in a smaller difference between pre-and post-brace scores.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a beneficial effect of a sports medicine-based rehabilitation program in conjunction with CDOs, resulting in improved performance and reduced pain. 3,[9][10][11] Therefore, a similar devicespecific clinical training program was integrated into the care pathway in an effort to achieve positive outcomes in a civilian population.…”
Section: Background and Significancementioning
confidence: 99%